Synthesis of 2, 4, 6‐Trisubstituted Pyrimidines via Iron‐Catalyzed Homocoupling of α, β‐Unsaturated Ketoximes. Issue 15 (5th July 2022) - Xu, Gaochen; Wang, Xuemei; Jia, Chenglong; Yan, Huan; Zhang, Sai; Wu, Qinghuan; Zhu, Ning; Fang, Zheng; Duan, Jindian; Guo, Kai
Abstract: A FeCl2 ‐catalyzed homocoupling of α, β ‐unsaturated ketoximes in batch and flow is reported. This protocol demonstrates broad substrate scope and functional group tolerance, providing an alternate route toward the synthesis of 2, 4, 6‐trisubstituted pyrimidines under mild conditions. Also a gram‐scale reaction has been performed to evaluate the applicability of this method. Abstract :